(untitled) (Journal of Renal and Hepatic Disorders, 2020)
Tacrolimus (FK506) is the most widely used anti-rejection drug in kidney transplantation, especially its extended release Tacrolimus formulation (ER-Tac, Advagraf), which is used when target blood levels can be difficult to reach in high metabolizer patients. In this retrospective monocentric study, we analyzed the effect of a switch from ER-Tac to LifeCycle Pharma Tacrolimus (LPCT, Envarsus) on the dose/level ratio of FK506 in high metabolizer patients that cannot achieve target blood levels in the first 6 months after transplantation. We observed a statistically significant improvement in the level to dose ratio after the switch. Renal function remained stable. We also observed a reduction in the development of tremors. Our data suggest that LPCT can be used in a safer way in high metabolizer kidney transplant recipients.